123I Scintigraphy Mirror Image of Graves Disease Induced by Radioiodine Treatment for Toxic Adenoma. (February 2022) - Lugat, Alexandre; Drui, Delphine; Bach-Ngohou, Kalyane; Guillot, Pascale; Mourrain-Langlois, Emmanuelle; Kraeber-Bodéré, Françoise; Ansquer, Catherine
Abstract : Abstract: A 61-year-old woman presenting with hyperthyroidism received 131 I therapy for a toxic adenoma diagnosed by 123 I scintigraphy. Six months later, the patient had a relapse of hyperthyroidism, and 123 I scintigraphy showed a mirror image of the first scintigraphy: a high and diffuse uptake in the thyroid gland except for the previously treated nodule. Graves disease was confirmed by elevated thyrotropin receptor antibodies. The patient was cured by a second radioiodine therapy. Radioiodine-induced Graves disease may occur within 6 months of 131 I treatment of toxic adenoma and can be treated with a second line of 131 I.